Depth-Resolved Imaging of Radiation-Induced Doping Changes in Silicon. (1st January 2015) - Dang, Z. Y.; Breese, M. B. H.
Abstract : We present a method for imaging variations in the doping depth profile in n- and p-type silicon induced by high energy ion irradiation. This doping microscopy method is based on electrochemical anodization of irradiated wafers, producing porous silicon with a local porosity depending on doping changes. In moderately-doped n-type silicon a higher porosity corresponds to where irradiation creates excess donors and a lower porosity corresponds to where acceptors are created. Higher porosity regions may be selectively removed and so observed in cross-section images. We compare the effects of proton and helium ion irradiation on the localized doping in n-type Czochralski silicon, with and without annealing at 300°C. Even at such a low annealing temperature, a pronounced n + doping is observed for helium irradiation, highly confined to just the irradiated volume. In comparison, proton irradiation results in weaker n + doping which extends beyond the irradiated region, attributed to hydrogen diffusion.